1995
DOI: 10.1159/000126853
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways Involved in GnRH Secretion in GT<sub>1</sub> Cells

Abstract: The GT1 GnRH neuronal cell lines exhibit highly differentiated properties of GnRH neurons. We have used GT1–1 cells to study the role of the cyclic AMP/ protein kinase A, cyclic GMP/protein kinase G and Ca2+/protein kinase C signaling pathways in the regulation of GnRH secretion. Superfusion of GT1–1 cells with the cyclic AMP analog 8-Br-cyclic AMP (0.5 and 2.5 mM) or the adenylate cyclase activator forskolin (1 and 10 µM) for 100 min increased the amplitude of GnRH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
62
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 8 publications
2
62
0
Order By: Relevance
“…We previously showed that GT1 cells expressed D1-DA receptors that were positively coupled to AC (8) and that increases in cAMP levels resulted in the secretion of GnRH (13). Since intracellular cAMP is rapidly exported out of a variety of cells (27), we asked whether we could simultaneously follow dynamic changes in GnRH and cAMP.…”
Section: Results Camp Regulation Of Gnrh Secretionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that GT1 cells expressed D1-DA receptors that were positively coupled to AC (8) and that increases in cAMP levels resulted in the secretion of GnRH (13). Since intracellular cAMP is rapidly exported out of a variety of cells (27), we asked whether we could simultaneously follow dynamic changes in GnRH and cAMP.…”
Section: Results Camp Regulation Of Gnrh Secretionmentioning
confidence: 99%
“…Treatment of GT1 cells with DA or NE increased intracellular cAMP levels and stimulated GnRH secretion in a dose-dependent fashion (8,12). The GnRH-releasing effects of DA and NE were mimicked by pharmacologically increasing the intracellular cAMP level with 8-Br-cAMP or forskolin treatment (13). The level of secretion of GnRH was proportional to the activation of AC and increases in cAMP levels.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…The secretion of GnRH in GT1 neurons is stimulated by elevations in cAMP levels (6)(7)(8). The stimulation of GnRH secretion by elevated cAMP levels appears to be regulated via cAMP-gated cation channels expressed by the cells.…”
mentioning
confidence: 99%